4-D MRI flow analysis in the course of interrupted aortic arch reveals complex morphology and quantifies amount of collateral blood flow. - Hirtler, Daniel; Geiger, Julia; Jung, Bernd; Markl, Michael; Arnold, Raoul (Pediatric Radiology, 2013)
We present findings in a 17-year-old with interrupted aortic arch, in whom standard imaging techniques missed functional and morphological problems. Flow-sensitive four-dimensional magnetic resonance (4-D MR) enabled assessment of the complex anatomy and blood-flow characteristics in the entire aorta and direct quantification of blood flow in collateral vessels. Our findings highlight the entire morphological and functional problem of interrupted aortic arch and illustrate the potential of flow-sensitive 4-D MR for surgical planning in congenital heart disease.